Continuous Local Infiltration Analgesia after TKA: A Meta-Analysis - Keijsers, Renee; van den Bekerom, Michel; van Delft, Rogier; van Lotten, Manon; Rademakers, Maarten; Nolte, Peter A. (The Journal of Knee Surgery, 2016)
The analgesic effect of local infiltration analgesia (LIA) after total knee arthroplasty (TKA) has been reported to be less than 24 hours. The concept of continuous LIA (CLIA) has been developed to achieve prolonged analgesia by bolus injections or by pump infusion of analgesics. The purpose of this meta-analysis is to assess the effect of CLIA versus single-shot injection LIA (SLIA) and placebo on pain after TKA.A systematic search was performed in most relevant databases to identify all randomized controlled trials (RCTs) comparing intra-articular CLIA with SLIA or placebo for TKA. Primary outcome measures were visual analogue scale (VAS)-scores after 24, 48, and 72 hours at rest and during activity. Data were extracted for meta-analysis and pooled using Cochrane software. The results of comparable studies were pooled using the fixed effects model or random effects model.A total of 11 RCTs were included. Five articles were eligible for meta-analysis comparing CLIA versus placebo, involving 227 TKAs. VAS scores at rest 24 hours after surgery were in favor of CLIA with a decrease of pain scores of 46%. On the second and third postoperative day, the decrease in VAS scores was no longer significant. During activity VAS scores were also in favor of CLIA after 24 and 48 hours.Two studies were eligible for meta-analysis comparing CLIA versus SLIA. VAS scores at rest, 48 hours after surgery, were in favor of CLIA. CLIA can possibly provide a reduced pain perception for 24 hours postoperative at rest after performing a TKA. This effect may persist until 48 hours postoperative during activity. Due to the high level of heterogeneity no firm further conclusions can be drawn.
Keywords: analgesia; arthroplasty; postoperative pain; TKA; knee